2022
DOI: 10.1007/s10694-022-01228-z
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study of the Fire Dynamics in a Semi-enclosure Formed by Photovoltaic (PV) Installations on Flat Roof Constructions

Abstract: Flame spread experiments upon a BROOF(t4) compliant flat roof mock-up located below a vertical barrier were carried out for variations in gap height, inclination, subjacent insulation material, and the barrier type (stainless-steel board or photovoltaic (PV) module). A binary flame spread scenario was identified, where re-radiation from the flame facilitated self-sustained flame spread if the gap height to the horizontal panel was below 10 cm for the stainless-steel board and 11 cm for PV modules. These were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The worst option in this case is a roof insulated only with polystyrene foam. Such a structure will require a layer that mitigates the effects of fire to prevent serious consequences (Kristensen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The worst option in this case is a roof insulated only with polystyrene foam. Such a structure will require a layer that mitigates the effects of fire to prevent serious consequences (Kristensen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PV systems are available in all sizes, from a single PV cell mounted on the wall of a power bank, to domestic and commercial installations on buildings, to ground installations of nearly 1 GW, such as the Longyangxia Dam Solar Park in China (Voiland, 2017). The increased number of photovoltaic systems is associated with a continuous reduction in the cost of photovoltaic modules and thus the cost of energy, which makes them attractive to commercial and family property owners (Kristensen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment conducted by Kristensen and Jomaas [ 12 ] indicated that the flame propagation is influenced substantially by the geometry of PV installations with additional heat reflected underneath panels that fuels fire to propagate. The inclination of the PV modules also affects the flame spread rate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%